Optimizing Inventory Management Using ABC Analysis and Visual Control: A Case Study of a Motorcycle Parts Warehouse in Samut Prakan - ขันธุ์วงค์, วนัสนันท์; เจริญศิริ , อภิญญา; โพธิ์เกษม, ภนิดา; ตั้งเด่นชัย, พิศุทธิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study solutions for product search issues and improve the quality of inventory storage, using a case study of a motorcycle parts warehouse in Samut Prakan Province. The tools applied to address the problems were the ABC Analysis theory and Visual Control theory. Data was analyzed using a Fishbone Diagram to identify root causes related to inventory management and guide the reorganization of stored items within the warehouse.The results of applying the ABC Analysis revealed that warehouse operations became more efficient. Prior to the research, employees worked without a systematic approach, resulting in lengthy product search times and production delays. After implementing the new methods, employees were able to reduce the time spent searching for products and increase production time by 22.60%. This improvement was achieved through the application of Visual Control, or symbolic tools, to systematically arrange products in the warehouse.Enhancing the inventory management process also enabled the company to clearly identify out-of-stock and overstock items, thereby improving the overall efficiency of inventory control.